Optimization of ultrasonic-assisted extraction of polyphenols from the polyherbal formulation of Cinnamomum verum, Origanum majorana, and Origanum vulgare and their anti-diabetic capacity in zebrafish (Danio rerio) - Rosa Martha Pérez Gutiérrez; Felipe Fernando Martínez Jerónimo; José Guadalupe Contreras Soto; Alethia Muñiz Ramírez; María Fernanda Estrella Mendoza (Heliyon, 2022)
The Cinnamomum verum (CV), Origanum majorana (CM), and Origanum vulgare (OV) have been used in traditional medicine in several regions of México for their anti-diabetic properties. In this study investigated the variables of ultrasound-assisted extraction for the polyphenolic compounds from the combination of these plants and explore their potential antidiabetic activities on glucose-induced-diabetic zebrafish. Determined the optimum conditions for ultrasonic-assisted extraction (UAE) to maximum recovery amounts of phenolic compounds from the extract of these plants. Polyphenols were detected in the extracts using HPLC-DAD-analysis. Extracts were evaluated on zebrafish exposed to high glucose concentration (110 mM) for two weeks. Results showed second-order polynomial mathematical models with a high coefficient of determination (R2 > 0.9564). Optimized extraction conditions for UAE from the combination of the 3 plants (COV) were as follows: 66.03%, ethanol, 28.87 min, and 21.51 mL/g for maximal flavonoids extraction. Used the same optimal extraction conditions for CV, CM, and OV. Results from LC-MS/MS indicated 9 polyphenolic compounds in CV, 12 in CM, and 6 in OV, the content of total polyphenols was 310.28, 90.42, and 126.74 mg GAE 100 g−1 dry weight, respectively. However, hyperglycemic fish showed an increase in cholesterol and triglyceride levels whereas extracts completely prevented these metabolic alterations. COV showed higher anti-diabetic ability than CV, CM, and OV, suggesting a synergistic effect between them. Our investigation developed a new herbal formulation of Cinnamomum verum; Origanum majorana; Origanum vulgare that has proven effective in animals with type 2 diabetes will form a new class of supplements to treat diabetic complications.